Extracellular vesicles: A new diagnostic biomarker and targeted drug in osteosarcoma - Gao, Xiaozhuo; Gao, Bo; Li, Shenglong (Frontiers in Immunology, 2022)
Osteosarcoma (OS) is a primary bone cancer that is highly prevalent among adolescents and adults below the age of 20 years. The prognostic outcome of metastatic OS or relapse is extremely poor; thus, developing new diagnostic and therapeutic strategies for treating OS is necessary. Extracellular vesicles (EVs) ranging from 30–150 nm in diameter are commonly produced in different cells and are found in various types of body fluids. EVs are rich in biologically active components like proteins, lipids, and nucleic acids. They also strongly affect pathophysiological processes by modulating the intercellular signaling pathways and the exchange of biomolecules. Many studies have found that EVs influence the occurrence, development, and metastasis of osteosarcoma. The regulation of inflammatory communication pathways by EVs affects OS and other bone-related pathological conditions, such as osteoarthritis and rheumatoid arthritis. In this study, we reviewed the latest findings related to diagnosis, prognosis prediction, and the development of treatment strategies for OS from the perspective of EVs.